Modernization on Balinese Proverbs to Express Someone’s Emotion - Claria, Dewa Ayu Kadek; Kardana, I Nyoman; Rajistha, I Gusti Ngurah Adi (International Journal of Psychosocial Rehabilitation, 2020)
Reveals the process of modernization on Balinese proverbs from the classic proverb into the modern proverb especially in expressing the emotions is quite importance lately. It was influenced by the lack of use of classical proverbs itself in the society nowadays which need to be discovered. The issues raised in this research are the existences of classical Balinese proverbs which have been influenced by modernization and the impacts of that situation on language use in the society. By using random questionnaire given to the local people which were divided into two groups; educated and non-educated, the data obtained was analysed based on qualitative-analytical method. The qualitative-analytical method is really relevant with this research to find out the language system and rules lies in linguistics characteristics which leads to the proverbs. The research brings us to the new concept of proverbs to express emotions in Bali by using Ecolinguistics parameters combined with the emotion concepts. The modernization was influenced by the approachment of another culture to the society including their languages, styles and a new mind-set that has been accepted by local people which bring a big impact to the classical proverbs. From sixteen types of Balinese proverbs which are still exists in Bali, not all of them affected by modernization. The emotion shown by the modern proverbs felt out the same meaning and purpose with the classical proverb. It can be concluded that the modernization affects the choice of lexical items but it does not change the meaning, message and culture which is contained in the classical proverbs. It confirms that the strong messages conveyed by the ancestors in Bali through proverbs has been psychologically attached and successfully passed in the society from generation to generation.